Application of Vocational Standards in the VET Field: Key Aspects and Risks - Blinov, Vladimir I. (International Journal of Psychosocial Rehabilitation, 2020)
The purpose – the analysis of application of vocational standards in professional education in Russia. Authors consider most frequently asked questions in connection with introduction of the document, new to the Russian professional community, – the vocational standard; compare advantages and shortcomings of official and activity approaches of the qualification requirements description; show possibilities of vocational standards use during the developing of duty regulations, assessment of qualification, represent the most difficult surmountable obstacles of mental character which are slowing down development of national system of qualifications of modern Russia. In article the methodology of comparative research on the basis of the analysis of domestic experience of qualifications system development during the Soviet and Post-Soviet periods is used. Methods of collecting empirical information on approaches to the characteristic of qualifications in modern vocational standards and ETKS, EKSD have been chosen; methods of the conceptual and terminological analysis, interpretation and modeling, problem method that has allowed to receive results: to reveal specifics of the technique of Russian vocational standards development, to characterize the arising risks of their application and to plan ways of overcoming risks. The scientific novelty of work consists in consecutive justification of need for transition from pro- Soviet qualification system to functional and activity one. The practical importance consists in justification of advantages of application of vocational standards in Russia.